2021
DOI: 10.3389/fpls.2021.756330
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Proteomic Profiling Reveal the Key Role of AcMYB16 in the Response of Pseudomonas syringae pv. actinidiae in Kiwifruit

Abstract: Kiwifruit bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa), is an important disease of kiwifruit (Actinidia Lind.). Plant hormones may induce various secondary metabolites to resist pathogens via modulation of hormone-responsive transcription factors (TFs), as reported in past studies. In this study, we showed that JA accumulated in the susceptible cultivar Actinidia chinensis ‘Hongyang’ but decreased in the resistant cultivar of A. chinensis var. deliciosa ‘Jinkui’ in response to Psa. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…deliciosa Jinkui but upregulated in the susceptible cultivar A. chinensis var. chinensis Hongyang in response to Psa, putatively indicating that MYB16 acts as a negative regulatory gene in response to JA in kiwifruit infected with Psa [143]. Concordantly, a significant increase in disease development was observed in plants treated with methyl jasmonate [134,151,152], and thus, it is currently acknowledged that Actinidia spp.…”
Section: Phytohormone Regulationmentioning
confidence: 91%
See 3 more Smart Citations
“…deliciosa Jinkui but upregulated in the susceptible cultivar A. chinensis var. chinensis Hongyang in response to Psa, putatively indicating that MYB16 acts as a negative regulatory gene in response to JA in kiwifruit infected with Psa [143]. Concordantly, a significant increase in disease development was observed in plants treated with methyl jasmonate [134,151,152], and thus, it is currently acknowledged that Actinidia spp.…”
Section: Phytohormone Regulationmentioning
confidence: 91%
“…deliciosa, such as Jinkui, resistant hybrids from A. chinensis var. chinensis Hort16A and of A. arguta, also pinpoint the key role of several of these TFs, including the R2R3-MYB and MYB48 families [139,140,143], in the regulation of ROS-and phytohormone-mediated signaling to finally determine plant tolerance [34,141,144,145].…”
Section: Pathogen Recognition and Triggered Immunitymentioning
confidence: 95%
See 2 more Smart Citations
“…MeJA regulates multiple plant processes, including organ development, cell cycle regulation, secondary metabolite biosynthesis, and defense responses to various biotic and abiotic stresses [ 3 , 4 ]. Increasing evidence has shown that MeJA plays a positive role in inducing cold stress tolerance in horticultural crops, such as mango [ 5 ], banana [ 6 ], kiwi [ 7 ], and pitaya [ 8 ]. Cold exposure rapidly induces the expression of JA biosynthesis-related genes, among which jasmonate-ZIM-domain (JAZ) proteins are important repressors of the JA signaling pathway.…”
Section: Introductionmentioning
confidence: 99%